Research on Pressure Relief Hole Parameters Based on Abutment Pressure Distribution Pattern - Jian Hao; Hua Bian; Yongkui Shi; Anfa Chen; Jiankang Liu; Peizhe Zhang; Linjun Peng; Jianquan Tang (Shock and Vibration)
Borehole pressure relief technology is an effective way to reduce the elastic energy in the surrounding rock of deep roadways, thereby reducing the risk of regional rock bursts. To avoid large deformation of the roadway caused by pressure relief holes with large diameters and insufficient pressure relief with small pore diameters, this study proposes precise pressure relief holes with nonequal diameters in order to achieve strong pressure relief with minimal disturbance based on the abutment pressure distribution pattern. To verify the pressure relief effect of the nonequal diameter holes, numerical simulations were performed in FLAC3D. This study investigated stress field, deformation laws, and plastic failure zone of roadway surrounding rock with 100 mm pressure relief holes, nonequal diameter precision pressure relief hole (100 mm + 300 mm), and 300 mm pressure relief holes. The simulation results show that, as the diameter of the pressure relief hole increases, the coupling effect of evenly spaced adjacent pressure relief holes is strengthened, thus improving the pressure relief efficiency. When pressure relief holes of nonequal diameter are adopted, the stress environment of the surrounding rock is clearly improved compared to100 mm pressure relief holes, and the plastic failure range increased by 2-3 times. The roof-to-floor convergence with nonequal diameter is 30.8% that of 300 mm pressure relief holes and 41% that of 100 mm pressure relief holes. Furthermore, the rib displacement is 30.4% and 46.9% that of 300 mm and 100 mm pressure relief holes, respectively. Thus, precise pressure relief holes with nonequal diameter provide both strong pressure relief associated with large diameter holes and small disturbance of small diameter of small holes. This study provides a reference for precise pressure relief application with pressure relief holes.